A novel non-Hertzian contact model of spherical roller bearings. (January 2016) - Xing, Yu; Xu, Hua; Pei, Shiyuan; Chen, Xiaolei; Liu, Xuejing
Aiming at describing the indeterminate contact status and acquiring the mechanical behavior of the spherical roller bearing, a novel method is proposed to establish the non-Hertzian contact model. The importance of the indeterminate contact status is illustrated by the comparisons with the computing results of the Hertzian contact model. In view of the computing accuracy and rate, the computing efficiency of the finite element model is lower than that of the non-Hertzian contact model for the mechanical analysis of the spherical roller bearing. The effects of the design parameters in spherical roller bearings are analyzed by the non-Hertzian contact model. An agreement is shown from the analysis results of the typical ball bearing and roller bearing whereby the correctness and versatility of the non-Hertzian model are verified.